2013
DOI: 10.1267/ahc.13037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Administration of Pilocarpine and Isoproterenol on Aquaporin-5 Expression in Rat Salivary Glands

Abstract: Aquaporins are water channel proteins which enable rapid water movement across the plasma membrane. Aquaporin-5 (AQP5) is the major aquaporin and is expressed on the apical membrane of salivary gland acinar cells. We examined the effects of repeated administration of pilocarpine, a clinically useful stimulant for salivary fluid secretion, and isoproterenol (IPR), a stimulant for salivary protein secretion, on the abundance of AQP5 protein in rat salivary glands by immunofluorescence microscopy and semi-quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
3
13
0
1
Order By: Relevance
“…In route 4, AQP5 is released into saliva by exosomes [12,13]. Route 5 is the trafficking route for AQP5 together with zymogen granules [59,60]. In this study, we showed that AQP5 was trafficked from the non-apical region to the nuclear membrane and APM together with sphingolipid-rich vesicles in parotid acinar cells upon activation of mAChRs.…”
Section: Closedmentioning
confidence: 56%
“…In route 4, AQP5 is released into saliva by exosomes [12,13]. Route 5 is the trafficking route for AQP5 together with zymogen granules [59,60]. In this study, we showed that AQP5 was trafficked from the non-apical region to the nuclear membrane and APM together with sphingolipid-rich vesicles in parotid acinar cells upon activation of mAChRs.…”
Section: Closedmentioning
confidence: 56%
“…The presence of AQP5 in acinar and ductal cells was widely discussed in literature, although its location and role in the physiology of saliva synthesis involve controversial aspects. Generally, AQP5 is described as seen in the apical membrane of acinar cells of rodents (Funaki et al, 1998;Delporte and Steinfeld, 2006;Li et al, 2006aLi et al, , 2006bTakakura et al, 2007;Larsen et al, 2011;Matsuzaki et al, 2012;Delporte, 2013;Susa et al, 2013;Takahashi et al, 2015) and humans (Gresz et al, 2001;Delporte and Steinfeld, 2006;Delporte, 2013), while some authors also described it in the basolateral membrane and cytoplasm of these cells (Larsen et al, 2011;Matsuzaki et al, 2012;Susa et al, 2013). Regarding the ductal cells, many studies diverge when it comes to its occurrence (Cherry and Glucksmann,1959;Delporte and Steinfeld, 2006;Takakura et al, 2007;Larsen et al, 2011;Matsuzaki et al, 2012) or absence (Funaki et al, 1998;Li et al, 2006aLi et al, , 2006b in the intercalated duct.…”
Section: Discussionmentioning
confidence: 99%
“…They also participate in many pathological processes such as glaucoma, epilepsy, obesity and cancer (Verkman, 2005(Verkman, , 2009. Acinar epithelial cells of salivary glands show high permeability to the passage of water, and therefore, have AQPs (Delporte, 2013;Aure et al, 2014;Delporte and Steinfeld, 2006;Matsuzaki et al, 2012;Takahashi et al, 2015;Takakura et al, 2007;Susa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are: the observation of subcellular distribution of lysozyme in the mouse major salivary glands, the intragranular compartmentation of this secretion enzyme and its relationship with α-amylase using light and electron microscopy [141]; the study of contraction of myoepithelial cells in the human submandibular gland using confocal microscopy [142]. Moreover, the combination of electrophoretic and immunohistochemical techniques have been used to evaluate the distribution and expression of several proteins, such as CA6 in minor and major salivary glands of humans [25,143], leptin and the functional leptin receptor in major salivary glands of humans [135], muscarinic receptor subtypes in salivary glands of rats, sheep and man [144], aquaporin water channels in rat major salivary glands [145,146], and cytoskeleton proteins in rat parotid glands [147].…”
Section: Microscopy Techniquesmentioning
confidence: 99%